Selectivity of metal oxide atomic layer deposition on hydrogen terminated and oxidized Si(001)-(2×1) surface - Longo, Roberto C.; McDonnell, Stephen; Dick, D.; Wallace, R. M.; Chabal, Yves J.; Owen, James H. G.; Ballard, Josh B.; Randall, John N.; Cho, Kyeongjae (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures, 2014)
In this work, the authors used density-functional theory methods and x-ray photoelectron spectroscopy to study the chemical composition and growth rate of HfO2, Al2O3, and TiO2 thin films grown by in-situ atomic layer deposition on both oxidized and hydrogen-terminated Si(001) surfaces. The growth rate of all films is found to be lower on hydrogen-terminated Si with respect to the oxidized Si surface. However, the degree of selectivity is found to be dependent of the deposition material. TiO2 is found to be highly selective with depositions on the hydrogen terminated silicon having growth rates up to 180 times lower than those on oxidized Si, while similar depositions of HfO2 and Al2O3 resulted in growth rates more than half that on oxidized silicon. By means of density-functional theory methods, the authors elucidate the origin of the different growth rates obtained for the three different precursors, from both energetic and kinetic points of view.